Japanese Bunker Banyuwangi Left As A Laboratory For Learning History - Miskawi Miskawi; Abdul Shomad (History Education, University of Jember, 2022)
There are many Japanese bunkers in Banyuwangi Regency, one of which is in Blimbingsari District. Bunkers have not been recorded and used as a source for historical knowledge. Considering that the goal of this study is (1) list the Japanese bunkers in Bimbingsari, Banyuwangi Regency, and (2) explain how they are used as a history learning lab. The descriptive-analytical research methodology was employed.. Information supplied through surveys, interviews, and literature reviews. A spatial method of data analysis was used. A scientific method is used when using bunkers in the educational process. According to the findings of the research, six bunkers with the designations BLB-BM 01, BLB-BM 02, BLB-BM 03, and BLB-BM 04 that are situated in Pantai Ria, Bomo Village, Blimbingsari, and Banyuwangi. Keywords: Bunker, Japan, Laboratory, Education, History